Studi Tentang Kepemimpinan Perempuan di Lingkungan Organisasi Badan Eksekutif Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman - Iin Ferolita; Marwiah Marwiah; Novita Majid (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
This research aims to find out women's leadership in the organizational environment of the Student Executive Board of the Faculty of Teacher Training and Education, Mulawarman University, and understand the strategies of the BEM FKIP UNMUL administrators to increase the role and participation of women's leadership and see the reality of women's leadership in BEM FKIP UNMUL. Basically, the type of research used is descriptive, namely research that attempts to provide an overview of the object being studied with the aim of creating a descriptive or systematic and actual picture of existing facts. The results of this research show that women's leadership in the BEM FKIP UNMUL environment to become a Governor has not been successful, but looking at women leading a field, agency or bureau and small work program, they are very competent.